2001
DOI: 10.1161/01.hyp.37.3.869
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of Isolated Systolic Hypertension Among Middle-Aged and Elderly US Hypertensives

Abstract: Abstract-The purpose of the present study was to examine patterns of systolic and diastolic hypertension by age in the nationally representative National Health and Nutrition Examination Survey (NHANES) III and to determine when treatment and control efforts should be recommended. Percentage distribution of 3 blood pressure subtypes (isolated systolic hypertension, combined systolic/diastolic hypertension, and isolated diastolic hypertension) was categorized for uncontrolled hypertension (untreated and inadequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
173
2
8

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 597 publications
(194 citation statements)
references
References 33 publications
11
173
2
8
Order By: Relevance
“…Although the original VA studies and the first versions of Joint National Committee guidelines have focused on diastolic BP alone, it was later realized that systolic BP is a stronger determinant of cardiovascular outcomes in hypertensive patients, especially in older age 23, 24, 25. Indeed, the management of study participants in the recent Systolic Pressure Intervention Trial was based on systolic BP levels alone, almost ignoring diastolic BP levels 11…”
Section: Discussionmentioning
confidence: 99%
“…Although the original VA studies and the first versions of Joint National Committee guidelines have focused on diastolic BP alone, it was later realized that systolic BP is a stronger determinant of cardiovascular outcomes in hypertensive patients, especially in older age 23, 24, 25. Indeed, the management of study participants in the recent Systolic Pressure Intervention Trial was based on systolic BP levels alone, almost ignoring diastolic BP levels 11…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Similarly, two recent studies have reported that SBP has a different impact than DBP on blood pressure staging. 4,6 To our knowledge, the SBP and DBP staging impact has only been reported in the US. 4,6,7 Nonetheless, the staging impact of SBP and DBP, as well as the community burden of elevated SBP and SBP and DBP levels, 22.5% were up-staged on the basis of their SBP, and 16.7% were up-staged on the basis of their DBP.…”
Section: Introductionmentioning
confidence: 93%
“…4,6 To our knowledge, the SBP and DBP staging impact has only been reported in the US. 4,6,7 Nonetheless, the staging impact of SBP and DBP, as well as the community burden of elevated SBP and SBP and DBP levels, 22.5% were up-staged on the basis of their SBP, and 16.7% were up-staged on the basis of their DBP. SBP alone thus correctly classified JNC-VI staging in 83.3% of subjects vs 77.5% for DBP alone.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…More important, most hypertensive patients have grade 1 hypertension (untreated systolic blood pressure [SBP] of 140–159 mm Hg and/or diastolic blood pressure [DBP] of 90–99 mm Hg) and no previous cardiovascular diseases 2. The decision to treat this population has important clinical (eg, adverse drug effects, lifetime of drug therapy) and public health (eg, high cost of drugs, medical services) implications 3.…”
Section: Introductionmentioning
confidence: 99%